A "Splash" of Taiwan Bubble Tea: Gastrodiplomacy, Nation Brand and A Symbol - Angelika Rachelina Putri; Riski M. Baskoro (AEGIS : Journal of International Relations, 2023)
Bubble Tea is one of the typical drinks of Taiwan, which has become known since the 1980s in Taichung, Taiwan. Bubble Tea is prevalent in various circles of society. With the recognition of Bubble Tea, the government of Taiwan took advantage of this opportunity to build a positive image amidst its conflict with China regarding the One China Policy.The Taiwanese government developed Bubble Tea as a national brand through gastrodiplomacy to introduce its signature drink to the world. A qualitative approach will be chosen in this study based on literature review withexploratory and descriptive approach. The author will use the concepts of gastrodiplomacy and nation branding. Also, this paper aims to prove how the Taiwanese government uses Bubble Tea not only as a typical Taiwanese drink but also as a symbol in the anti-China movement. The results of this study examine the Taiwanese government's efforts to utilize Bubble Tea as a disparities between China and Taiwan culture that can differentiate Taiwan from China.